Flower-shaped ALOOH nanostructures synthesized by the reaction of an AlN/Al composite nanopowder in water - Bakina O. V. Olga Vladimirovna; Svarovskaya N. V. Natalia Valentinovna; Glazkova E. A. Elena Alekseevna; Lozhkomoev A. S. Aleksandr Sergeevich; Khorobraya E. G. Elena Gennadjevna; Lerner M. I. Marat Izrailyevich (2015, 2015)
Title screen